ANALISA KELAYAKAN USAHA DAN PEMASARAN SARI BUAH JERUK MANIS DI UD MARGO MULYO DAU MALANG - Gatut Suliana; Endang Rusdiana (BUANA SAINS, 2010)
The aimed of this research was to calculate and analyze the feasibility and level of sweet orange juice marketing at UD Margo Mulyo. This research is descriptively through interviews and observation. The result showed that BEP units per year was 40.686,84 and Rp. 32.549,31. Its means also that this industry was appropriate to continue and has benefit of net sales above 33.000 units and for Rp. 23.760.000. Time required to return all of the cost was 2 years and 9 months, which means the return of all costs incurred earlier than 10 years. Bank loans amounting to 80% of the total capital Rp.95.865.500, and interest is 14%, and during the five-year period was Rp. 10.736.936. Installment loan per year is Rp.15.338.480 with interest on the loan per year was Rp. 2.147.387,2. In calculating the IRR was getting the 43%, which means the industry is appropriate to proceed because the IRR is greater than the interest rates offered by banks. Prices of goods manufactured was Rp. 509,920. Distribution system does not deal directly with retailers, but through marketing agencies. Marketing section includes not only market distribution, but also supervise and attract products that expired. Marketing flow of sweet orange juice producer to the consumer through marketing channels of three types namely (1) Line I, which Manufacturer to Dealer to Dealer Collector to Merchant Retailers; (2) Channel II is the Manufacturer to Dealer to Dealer Retailer; and ( 3) Line Producer III of the Merchant to Merchant Retailers Collectors